PENGARUH KEMAMPUAN KOMUNIKASI MATEMATIS DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA - Jenny Patricia Ayu Kai; Evi P. Hulukati; Ismail Djakaria (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
The aims of this research were to determine: (1) the impact of mathematical communication skills on learning outcomes, (2) the impact of learning motivation on learning outcomes, and (3) the simultaneous impact of mathematical communication skills and learning motivation on learning outcomes. This research was conducted at SMP Negeri 1 Botupingge and involved 23 respondents who were determined by using simple random sampling. The data collection techniques in this research employed instruments of: (1) test of mathematical communication skills, (2) learning motivation questionnaires, and (3) data on studentsâ€™ daily test result in class VII in algebra topic in odd semester. The research data were analyzed with descriptive statistics and inferential statistics with multiple regression analysis. Based on the findings, it can be inferred that: (1) mathematical communication skills impacted learning outcomes, (2) learning motivation impacted learning outcomes, and (3) simultaneously, mathematical communication skills and learning motivation impacted learning outcomes.Â